PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS KONSUMEN PADA BARBERSHOP KANG CUKUR DI PAGEDANGAN KABUPATEN TANGERANG - Akbariko, Saldi; Dewi, Widya Candra (Publika Citra Media, 2025)
This study aims to analyze the effect of service quality and price on consumer loyalty. The population in this study were all consumers of Kang Cukur Barbershop as many as 5,050 respondents. The research sample used a random sampling technique using the Slovin formula as many as 100 people. The method used in this study is a quantitative method. The data used in this study are primary data in the form of distributing questionnaires to consumers of Kang Cukur Barbershop who have been used as research samples. Data processing and analysis techniques use multiple regression analysis techniques. Simultaneous Significance Test of service quality on consumer loyalty obtained a value of t count> t table or (11.264> 1.984) thus H0 is rejected and H1 is accepted, while in the t test of Price on Consumer Loyalty obtained t count> t table or (6.623> 1.984) thus H0 is rejected and H1 is accepted. Hypothesis testing obtained a value of F count> F table or (79.970> 3.090). The results of the research test of service quality and price have a positive and significant effect on consumer loyalty with the regression equation Y = 4.762 + 0.567X1 + 0.341X2. The correlation coefficient value of 0.789 means that it has a strong relationship. The determination coefficient value is 62.2% while the remaining 37.8% is influenced by other factors. Thus H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence of service quality and price on consumer loyalty